Costo Utilidad de Colágena Polivinil-Pirrolidona en el Tratamiento de Osteartrosis de Rodilla en México (2014)
ABSTRACT: To assess the cost-utility of collagen-polyvinyl pyrrolidone (collagen-PVP), a new drug developed and manufactured in Mexico, compared to non-steroidal anti-inflammatory drugs in the treatment of patients with knee osteoarthritis (OA) in Mexico. Methods: A probabilistic Markov model with a lifetime horizon was designed to evaluate the costs and outcomes (QALYs) of collagen-PVP compared to NSAIDs in patients with OA. Data from randomized clinical trials conducted in México were obtained as input for probabilities. Utility values were elicited from international publications and costs information and service utilization was obtained from official publications of the Instituto Mexicano de Seguro Social - IMSS. Cost per quality adjusted life-years was calculated by using the Mexican Healthcare payer perspective. A discount rate of 5% for both cost and outcomes was used. Sensitivity analyzes were performed with variations in the parameters of gender, age, and price of collagen-PVP. Results: Patients treated with collagen-PVP showed a gain of 6.62 QALYs compared with 5.36 in patients with NSAIDs. The cost-utility ratio was higher in the NSAID group (MEX$ 170,010.76/QALY) compared to collagen-PVP (MEX $ 130,953.63/QALY). The incremental cost-utility ratio was MEX $ 35,194.16. Conclusions: This is the first economic evaluation of a new medication developed in Mexico and conducted partially with local data. The results of this study allow concluding that collagen-PVP is deemed as the dominant alternative compared with NSAIDs in the treatment of knee osteoarthritis.